Teacher Instructional Competence and Learners Performance in Social Studies: Basis for Enhancement Program - Pacuno, Nestor; Sanchez, Alex (JPAIR Multidisciplinary Research, 2020)
One of the goals of today’s pre-service and in-service training of teachers is to promote teacher’s competencies. According to the Department of Education, it is a big factor in the academic achievement of the students. Included under teacher competencies are teaching effectiveness, professional recognition and awards, membership and participation in professional organizations, scholarly abilities, and creative productiveness, and university and community service. In the daily life of students, they encounter different kinds of teachers. The purpose of this study is to determine the teachers’ Instructional competence and the students’ MPS and quarterly grade performance involving 46 respondents in the City Schools Division of Laguna. The level of teachers’ instructional competence of the teachers and principals Competence in curriculum content, Competence in transmitting the content to the learners, Competence in preparation of lesson log/plan, Competence in preparation of students’ engagement, Competence in classroom management; and Competence in providing conducive learning environment are interpreted as very satisfactory. The level of learners’ quarterly grade and MPS were fairly satisfactory for the grade and low mastery level for MPS. There is a significant difference between learning environment competence and learners’ quarterly grade and MPS. But there is no significant difference between the four aforementioned variables between learners’ quarterly grades and MPS.